KORELASI KADAR TUMOR NECROSIS FACTOR -Î± (TNF-Î±) DENGAN SKOR CHILD-PUGH PADA PENDERITA SIROSIS HATI - , ZIDNI SETYANINGRUM, dr. Neneng Ratnasari, SpPD-KGEH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background.Cirrhosis of the liver is the terminal stage liver disease that is irreversible with high morbidity and mortality. Assessment the severity of liver cirrhosis is based on Child-Pugh score. Tumor Necrosis Factor-Î± (TNF-Î±) is proinflammatory cytokine that is associated with the severity of liver cirrhosis. Level of TNF-Î± describes severity and extent of liver damage. Aim. The aim of this study is to investigate a correlation between elevated level of TNF-Î± with elevated Child-Pugh score in patients with liver cirrhosis. Methods. A cross-sectional study was conducted in November 2010 until November 2011. Subyek research were patients with liver cirrhosis who went to a clinic gastroenterohepatologi and in the department of internal medicine wards Sardjito Hospital in Yogyakarta. Collecting data is done by history, physical examination, abdominal ultrasound and blood chemistry measuremen. The level of TNF-Î± were measured by ELISA. Correlation analysis using Spearman's test. Results. A total subjects were 36 patients with mean of age 54.1 Â± 11.4 years old. Median TNF-Î± level was 28.05 pg / ml (19.4 to 90.4 pg / ml). Median Child-Pugh score was 8 (5-13). There is a very weak positive correlation which statistically not significant between the levels of TNF-Î± with Child-Pugh score in patients with liver cirrhosis (r = 0.07, p = 0.6). Conclusion.There is no correlation between elevated level of Tumor Necrosis Factor-Î± (TNF-Î±) with elevated Child-Pugh score in patients with liver cirrhosis.